SMN Kitchen Bergedil / Siti Sharifah Nur Ismail @ Mustapha - ISMAIL (a) MUSTAPHA, SITI SHARIFAH NUR (2017)
This business of "Tauhu Bergedil" product by SMN KITCHEN BERGEDIL are provide customer with delicious food can become evening snack and also an appetizer in social media through Facebook account and can see all mine business from there. While our competitor is very largest but were not giving up to post all in daily, a week and a month to make interesting to buyer's attractive to buy .SMN KITCHEN BERGEDIL is an ambitious to get known as a Frozen Fast food industry in the world. I have the main ambition to increase and maintain the quality in Frozen fast food industry. Their aim is to capture the Frozen Food market. Basically, I want to provide my products to anyone that is why they expanding their branches in all over the world. They want to increase their profit through